2014
DOI: 10.1371/journal.pone.0093082
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of HLA-A, -B, and -DRB1 Allele and Haplotype Frequencies of 21,918 Residents Living in Liaoning, China

Abstract: HLA-A, -B and -DRB1 allele frequencies and their haplotype frequencies in 21,918 Chinese residents living in Liaoning Province, who were registered as volunteer donors of China Marrow Donor Registry, were investigated. They are composed of 93.37% Han Chinese, 5.1% Manchus, 0.57% Mongols, 0.46% Hui persons, 0.29% Koreans and 0.14% Xibe ethnic group. In total eighteen different HLA-A alleles, forty-eight different HLA-B alleles and fourteen different HLA-DRB1 alleles have been identified. Their frequencies are i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 25 publications
3
21
0
Order By: Relevance
“…Pairwise F ST values calculated by arlequin software among 13 different populations. The genetic distance is indicated by the depth of the colour in the crossing area of pairwise populations DL: Dalian; LN: Liaoning (Li et al ., ); YW: Yantai‐Weihai (Zhang et al ., ); SH: Shanghai (Du et al ., ); KOR: Korea (Whang et al ., ); NEA: North‐east Asia; SEA: South‐east Asia; SWA: South‐west Asia; AUS: Australia; EUR: Europe; NA: North America; SSA: Sub‐Saharan Africa; BRA: Brazil (Macêdo et al ., ). NEA, SEA, SWA, AUS, EUR, NA and SSA data were obtained from http://www.ncbi.nlm.nih.gov/projects/gv/mhc/main.fcgi?cmd=init.…”
Section: Resultsmentioning
confidence: 99%
“…Pairwise F ST values calculated by arlequin software among 13 different populations. The genetic distance is indicated by the depth of the colour in the crossing area of pairwise populations DL: Dalian; LN: Liaoning (Li et al ., ); YW: Yantai‐Weihai (Zhang et al ., ); SH: Shanghai (Du et al ., ); KOR: Korea (Whang et al ., ); NEA: North‐east Asia; SEA: South‐east Asia; SWA: South‐west Asia; AUS: Australia; EUR: Europe; NA: North America; SSA: Sub‐Saharan Africa; BRA: Brazil (Macêdo et al ., ). NEA, SEA, SWA, AUS, EUR, NA and SSA data were obtained from http://www.ncbi.nlm.nih.gov/projects/gv/mhc/main.fcgi?cmd=init.…”
Section: Resultsmentioning
confidence: 99%
“…1A). 31,32 In this paper, we report the optimized design of a multi-epitope vaccine that takes into account all of these issues. Several elements were considered for our multiple-epitope vaccine design: epitope selection, epitope location, and linkers between epitopes.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the results showed that HLA‐A*33:03~B*58:01~DRB1*03:01 is the most common haplotype in the Nanning Han population, which is similar to the southern Chinese population and southern East Asia populations (Ding et al, ; He et al, ; Hoa et al, ; Lai et al, ; Shi et al, ). However, HLA‐A*30:01~B*13:02~DRB1*07:01 is the most frequent haplotype in the north Han populations but less common in the Nanning Han population (Li et al, ; Shao et al, ). In fact, it just reflects the general north–south genetic differentiation observed in many studies focusing on HLA alleles (Di & Sanchez‐Mazas, ) or other genetic markers, especially for markers on Y chromosomes and mitochondrial DNA (mtDNA; Zhang, Su, Zhang, & Jin, ).…”
Section: Discussionmentioning
confidence: 99%
“…The human MHC is human leucocyte antigen (HLA) system. HLA is located on the chromosome 6 in the 6 P 21.31 region and is the most polymorphic genes in the human genome (Li et al, ). To date, January 2018, total of 17,695 HLA alleles have been identified according to the IMGT/HLA Database (release Version 3.31.0).…”
Section: Introductionmentioning
confidence: 99%